MOBILITAS PEKERJA DARI DESA MAUMBI KE KOTA MANADO - Dewi ., Tambuwun; Leonardus R. Rengkung; Charles R. Ngangi (Sam Ratulangi University, 2016)
Mobility is the movement of people from one region to the other region within a specified period. In other words, mobility is the movement of people to make the shift from a region or area of origin to other regions. As the capital of North Sulawesi, Manado and surrounding area have the role of mutual support between regions, where the City of Manado regarded as an area that became the purpose of work. The interdependence of the region between Manado and surrounding areas also can be seen in the relationship between the city of Manado with Maumbi village as an area of support, in terms of both formal and informal workers who worked in Manado. The increasing number of such workers has contributed to greater mobility of workers from Maumbi Village to Manado. This study aims to determine the mobility of wokers from the village Maumbi to Manado based on the push and pull factors of mobility. In answering this purpose of this study the collected primary data and secondary data have conducted. The sampling technique used purposive sampling method. While secondary data taken at the village office Maumbi include the state of the last inhabitants in 2014, according to the number of people living in 2014 and the Maumbi Village community who work in the city of Manado. The variables measured were age, family size, length of stay, education level, number of family members working in Manado, type of work, number of dependents, total revenues, total expenses, mileage, travel time, type of transport, and cost of transportation. Analysis of the data used is descriptive analysis by describing and explaining all the factors related to the mobility of workers from the village Maumbi to Manado. The results showed that the pull factor mobility of the village Maumbi to Manado occur due to the distance traveled, the type of transport, length of stay, number of family members, income, expenses, and transportation costs, while pull factor mobility occurs because, type of work, education , age, and number of family members who work in the city of Manado.